Income Tax and Salary Liability Incentives: Microenterprise Law Highly Availed Privileges - Manipol, Vergel S. (Future Science / FSH-PH Publications, 2025)
This study evaluates the operational impact of two key incentives under the Barangay Micro Business Enterprises (BMBE) Law (Repub-lic Act No. 9178): Exemption from Income Tax & Fees (mean rating: 3.71) and Exemption from the Coverage of Minimum Wage Law (mean rating: 4.12). Through a quantitative survey of 192 regis-tered microenterprises, the study analyzed how these provisions in-fluence business sustainability and policy outcomes. For the first in-centive, Exemption from Income Tax & Fees, findings confirm its role in stimulating microenterprise growth without compromising na-tional fiscal stability. Aligning with Zax’s (2018) framework on tar-geted tax exemptions, the law achieves policy goals while minimizing economic distortions. However, enhanced monitoring mechanisms and adaptive tax schemes are recommended to balance relief with equitable economic participation. The second incentive, Exemption from the Coverage of Minimum Wage Law, reveals a dual effect: while employees face short-term income constraints, microenterprises pri-oritize sustained employment over strict wage compliance. Resource limitations among owners hinder adherence to wage standards, un-derscoring the need for interventions like microfinancing and target-ed subsidies. Such measures could reconcile operational viability with improved employee welfare. These results emphasize the necessity of incentive frameworks that empower microenterprises while safe-guarding employee interests. Structuring policies around adaptive monitoring, equitable resource access, and long-term employment stability can enhance the BMBE Law’s effectiveness. By addressing these dual imperatives, policymakers can foster microenterprise re-silience without undermining broader economic equity.